2009
DOI: 10.1149/1.3133182
|View full text |Cite
|
Sign up to set email alerts
|

Application of Surface Roughness Data for the Evaluation of Depth Profile Measurements of Nanoscale Multilayers

Abstract: A secondary neutral mass spectrometric ͑SNMS͒ depth profile study of electrodeposited Co/Cu multilayers was performed. Depth profile measurements were performed both in the conventional way ͑i.e., starting the sputtering from the final deposit surface͒ and in the reverse manner ͑i.e., detaching the multilayers from the substrate and starting the analysis from the substrate side, which was very smooth as compared to the final deposit surface͒. The latter method could yield significantly larger intensity fluctua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…The envelope curve of the decay of the composition oscillation for depths beyond 300 nm is mainly determined by the development of the surface roughness of the sample. 46 At high depth, where the planar sputtering front crosses the tilted layer interfaces randomly, a smearing out of the concentration profile can be observed.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…The envelope curve of the decay of the composition oscillation for depths beyond 300 nm is mainly determined by the development of the surface roughness of the sample. 46 At high depth, where the planar sputtering front crosses the tilted layer interfaces randomly, a smearing out of the concentration profile can be observed.…”
Section: Methodsmentioning
confidence: 98%
“…The surface of the resulting Cr-capped sample was as smooth as the Si wafer, making it particularly appropriate for a depth profile study. In order to achieve a sufficient spatial resolution along the depth, 46 the individual layer thicknesses in the Co/Cu(Ag) multilayers prepared for the SNMS study were chosen as high as 10 or 15 nm whereby keeping an equal thickness for the magnetic and non-magnetic layers. The total thickness of the SNMS multilayers was 400 or 450 nm.…”
Section: Methodsmentioning
confidence: 99%
“…This new technique named as the reverse depth profile analysis [34][35][36] has shown that in ED Fe-Co-Ni alloys various zones were formed close to the substrate due to the interplay of the anomalous nature of the codeposition of Fe, Co and Ni with the depletion of the electrolyte for the ions of the magnetic elements. The composition depth profile measured [36] did not agree with any of the thickness dependence of the composition reported earlier.…”
Section: Introductionmentioning
confidence: 99%
“…A 5-nm-thick Cr adhesive layer was followed by a 20-nm-thick Cu conductive layer; both layers were produced by evaporation. The mean surface roughness of the Si/Cr/Cu substrates determined with atomic force microscopy was found to be between 1 and 3 nm [21]. A Cu sheet served as counterelectrode in each case.…”
Section: Methodsmentioning
confidence: 99%